LA FIGURA DE IFIGENIA EN LA TRAGEDIA DE AGAMENÓN. DE LA LITERATURA GRIEGA A LA DRAMATURGIA ESPAÑOLA CONTEMPORANEA - Paco Serrano, Diana de (Myrtia, 2001)
The study reviews the works of classical literature which refer to Iphigeneia, the sacrificed daughter of Agamemnon, with an aim to analysing the function performed by her presence or absence in the collective story of the tragedy of the Atrides after the Trojan War. Iphigeneia comes to be presented her as a symbol of sacrifice in the allusions of other characters, but on occasion she is also made into the principal motive for Clytemnestra's murder of Agamemnon. In Aeschylus, Sophocles and Euripides as well as in Seneca and certain versions in the later tradition, the virgin's sacrifice is given a social and individual dimension, depending on the particular perspective of the author alluding to her story. After reviewing these works, the study presents several examples of the figure of Iphigeneia recreated from classical patterns in contemporary Spanish theatre, and considers the significance of her appearance or omission in modern dramatic texts.